SharePoint Framework for Developers: 3 Deployment, Upgrades, and Lifecycle. - Malik, Sahil (linkedin.com, 2018)
In this practical course—the third installment in a series—learn how to deploy SPFx solutions and manage their upgrades, and explore the ALM APIs.